2023
DOI: 10.2147/jir.s398282
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Fibronectin Exerts Beneficial Effects in Reducing Tissue Damage and Modulating Macrophage Function in a Murine Septic Model

Abstract: Background: Fibronectin (FN) can improve organ function and slow the progression of sepsis, but full-length FN is hard to be exacted as a therapeutic.Objective: This study aimed to investigate the beneficial effects of C-terminal heparin-binding domain polypeptide of FN (rhFNHC-36) in a cecal ligation and puncture (CLP)-mediated murine septic model and explore its regulatory effects on macrophages. Methods: Mice were randomly assigned to four groups: unoperated control (Normal), sham operation control (Sham), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, most studies report these damages 24h after CLP when our evaluation is 20h post-CLP, even though other studies shown early damage in mice before 20h post-CLP [11,17].…”
Section: Discussionmentioning
confidence: 87%
“…However, most studies report these damages 24h after CLP when our evaluation is 20h post-CLP, even though other studies shown early damage in mice before 20h post-CLP [11,17].…”
Section: Discussionmentioning
confidence: 87%
“…In humans, although contradictory findings have been reported, a general reduction of FN plasma levels was observed during acute inflammation associated with sepsis [ 13 ] coupled with increased production of circulating FN containing EDA [ 46 , 47 ]. Despite this, the concentration of plasma FN_EDA+ in patients with sepsis who survived was significantly lower than that in non-survivors [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, although contradictory findings have been reported, a general reduction of FN plasma levels was observed during acute inflammation associated with sepsis [ 13 ] coupled with increased production of circulating FN containing EDA [ 46 , 47 ]. Despite this, the concentration of plasma FN_EDA+ in patients with sepsis who survived was significantly lower than that in non-survivors [ 13 ]. Whether this is indirectly marking the ability of FN_EDA + to opsonize bacteria and favour the elimination of the complex or increased deposition in tissues during acute and severe inflammation is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zusanli (ST36), Guanyuan (CV4), and Qihai (CV6) acupoint electroacupuncture modulated the immune function of sepsis patients through the PD-1/PD-L1 pathway and improved clinical symptoms (169). Furthermore, adoptive transfer of bone marrow-derived dendritic cells (BMDCs), niacinamide nucleoside supplementation, fibronectin FN C-terminal heparin-binding domain polypeptide (rhFNHC-36), glutamine (GLN), recombinant enhancer of zeste homolog 2 (EZH2) inhibitor GSK343, mitogen-activated protein kinase phosphatase 1 (Mkp-1), mycophenolate mofetil (MMF), anti-ICAM (intercellular adhesion molecule)-1 antibody and other methods have shown improved survival rates in septic mice (178)(179)(180)(181)(182)(183)(184). Notably, downregulation of PD-L1 expression has been observed in these approaches.…”
Section: Preclinical Studiesmentioning
confidence: 99%